THE DEVELOPMENT OF CONTEXTUAL LEARNING-BASED COMIC MEDIA TO IMPROVE READING INTEREST IN 3RD GRADE STUDENTS OF SD NEGERI KARUNDANG 2 - Tri Astuti; Sholeh Hidayat; Isti Rusdiyani (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThe development research is carried out in accordance with the needs analysis of the problem in the form of the development of contextual learning-based comic media with the aim to analyze and describe: (1) The development of contextual learning-based comic media to improve students’ reading interest of 3rd grade, (2) Feasibility of contextual learning-based comic media in increasing students’ reading interest of 3rd grade (3) Responses and interest in reading of students to contextual learning-based comics media in increasing students’ reading interest of 3rd grade. This research is in the form of development research (R&D) with the ADDIE model through interview and questionnaire techniques in the 3rd grade of SDN Karundang 2 Academic Year of 2020/2021 with a total of 22 students. The feasibility test by validators of media experts and material experts obtained a score of 85% on the very feasible category. The results of the use of comic media in learning obtained a student response score of 88.5% in the very good category, in the reading interest test was 88% in the very high category.Keywords: Contextual Learning-Based Comic Media; Reading Interest